Urban farming and vertical farms: prospects for agricultural production in cities - Ivanikov, Valerii (Запоріжжя: НБ ТДАТУ, 2025)
Urban agriculture is the cultivation, processing and distribution of food within urban and suburban areas. One of the most promising forms of urban agriculture is vertical farming, a multi-level structure that allows plants to be grown in a controlled environment.The growing urban population (more than 68% of the world’s population is expected to live in urban areas by 2050, according to the UN, 2019) and the shortage of arable land are driving the search for innovative agricultural technologies to ensure food security within urban areas.
Keywords: hydroponics; aeroponics; integrated nutrition systems; urban farming